The African swine fever virus B125R protein antagonizes JAK-STAT signalling by promoting the degradation of IFNAR2 - Jun-Hao Fan; Yan-Yan Zhao; Yu-He Ma; Xiao-Ya Pan; Han-Cheng Shao; Meng-Hui Zi; Haojie Ren; Yuhang Zhang; Shichong Han; Bo Wan; Gai-Ping Zhang; Wen-Rui He (Veterinary Research)
Abstract African swine fever (ASF) is a highly contagious and severe hemorrhagic disease caused by African swine fever virus (ASFV). Currently, few safe and effective vaccines or antiviral drugs are available for its prevention. Interferon (IFN), a key component of innate antiviral immunity, induces interferon-stimulated genes (ISGs) by activating the JAK-STAT signalling pathway, resulting in antiviral effects. ASFV strains, including ASFV SY18, ASFV HLJ18, and ASFV BA71V, are highly sensitive to IFN-I treatment; however, the mechanisms by which ASFV antagonizes the host type I IFN response have not been fully elucidated. In this study, we identified the ASFV B125R protein (pB125R) as a negative regulator of the JAK-STAT pathway. We observed that ectopically expressed pB125R significantly suppressed the IFN-β-triggered activation of JAK-STAT signalling in HEK293T and PK-15 cells. Mechanistic studies revealed that pB125R binds to IFNAR2 and promotes its autophagic degradation, impairing the signal transduction of the IFN response at an early stage. This ultimately reduces the nuclear translocation of the ISGF3 complex and decreases ISG production. Our findings highlight the immunosuppressive activity of pB125R and reveal a novel mechanism by which ASFV evades the host IFN response, contributing to potential strategies for developing vaccines and therapeutics against ASF.